The Toxic Side of Nanotechnology: An Insight into Hazards to Health and the Ecosystem - Yadav S.K.; Khan Z.A.; Mishra B.; Bahadur S.; Kumar A.; Yadav B. (My University, 2025)
The objective of the present article is to provide an insight into the toxicity aspects of nanoparticles on health and the ecosystem, along with risk assessment and monitoring. After a detailed screening of various research reports from peer-reviewed journals, books, and research news, the article was prepared. Nanotechnology's various significant advantages over conventional technologies have been explored for diverse research and commercial needs, such as cosmetics, medical, pharmaceuticals, biotechnology, electronics, catalysts, and robotics. However, nanotechnology has several challenging elements for health, environment, society, economic growth, and unpredictable consequences due to its unknown nature, which needs to be identified. Therefore, in this review, an attempt has been made to cover the two most important aspects of the toxicity of nanoparticles, i.e., influence on health and the ecosystem. The health hazards to various organs, especially lungs, gastro-intestinal tract and dermis, and aquatic organisms, have been elaborated. Furthermore, various ecotoxicological aspects, including mechanism of ecotoxicity, ecotoxicological challenges, and solutions to be undertaken by ecotoxicologists, are discussed. Finally, risk assessments related to the approaches that can be used for the optimization of nanotechnology are also mentioned. It is high time that nanotechnology gets reconsideration and uncompromising attention at the public and private level regarding its use, handling, storage, proper treatment, and disposal. Also, risk analysis and establishment of regulatory guidelines for the optimization and safe practice of nanotechnology for humans less harmful to the environment are recommended. © 2022 Bentham Science Publishers.